Pregando resistência em tempos sombrios : responsabilidade como resistência ao nazismo nos sermões de Dietrich Bonhoeffer (1932-1937) - Karina Fonseca Soares Rezende (2022)
The present master’s thesis aimed to understand the political-religious resistance of the German Lutheran preacher and theologian Dietrich Bonhoeffer from the study of his sermons between 1932 and 1937 in three different places: Berlin, London and Finkenwalde. The main goal was to analyze the formation of an Ethic of Christian Responsibility from two strands codependent and corelated: amor mundi, in other words, the responsibility the Christian person has towards God and the Church which they belong. In this regard, 40 sermons from this period were analyzed, which are present in the collection Dietrich Bonhoeffer Work in English volumes 12, 13 and 14 e the original documentation available at the Staatsbibliothek in Berlin. Setting the preacher’s acting and livingness context in the three mentioned places, 380 documents were consulted as letters, memorandums, lectures and his teaching class drafts from Berlin University and the Finkenwalde preacher’s seminary, as well as the main books published of the author. The investigation of the sermons was guided on the discourse analysis of the drafts and sermons records in dialogue with the realms of History of Ideas, Political Philosophy, linked to Theological, Philosophical and Contemporary Historiography areas. It sought the deepening of the concepts, subjects and metaphors mobilized by him using biblical narratives as triggers to political discussions in his context and the understanding of preaching as a way of discursive political resistance to totalitarianism. From the analysis of the sermons, documentation not commonly used on the studies about the theologian, it is possible to realize the relevance of pastoral dimensions in the political-religious resistance to Nazism in the moments of its rise, consolidation and peak of the Third Reich in Germany.